UNIFICATION OF TERMS - THE REQUIREMENT OF TIME - Makhambetova, Айгүл Көбейсінқызы; Ainabayeva , Қымбат Әбілқайырқызы (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2018)
For any branch of linguistics the question of terminology is one of the most urgent. The titles of special definitions and terms, the system of definitions require special study. When identifying the lexical features of the language, the system and the description of definitions within the framework of terminology indicate that an analysis of language norms is required. The formation of international terms in the Kazakh terminology, the history of origin and its types are appeared in the reflections of scientific definitions. In the article, when applying borrowed words or translating into Kazakh, questions on etymological basis, semantic content, grammatical structure of terms, as well as regarding alternatives in other languages, are analyzed. Today, the role of translation in the formation of legal terms used in international documents is a pressing issue. Comprehensive information on legal linguistics, the correct use of legal terms in the state language, the combination of lexical norms and legal are provided. Clarity and concreteness of the legal content of the law are interrelated with the correct translation of terms into the state language and with the terminological specifics of legal linguistics. The process of implementation of new terms requires further development and modernization of the terminology of the Kazakh language and the norms of the culture of speech, therefore, the legitimacy of the application. Information on the formation and stabilization of language norms, as well as other issues in the framework of the considering problem are analyzed. State pays attention at and takes concrete steps to further improvement and systematization of terminology. Today, the terminology is expanding, and special branches are complemented by their own new titles. The basis of unification in terminology should begin with the correct formation of legal terms in the state language and combination of the lexical norm with the legal one. The development and formation of terminology is peculiar. We will not be mistaken if we say that this is connected with the ongoing political, economic, spiritual, cultural, historical and social changes in public life. The opinions of scientists who studied the history of the development of Kazakh terminology are not passed over.